2014
DOI: 10.1177/1049909114547945
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style Dimensions Can Affect Prolonged Grief Risk in Caregivers of Terminally Ill Patients With Cancer

Abstract: Female gender, high levels of depression, and preoccupation with relationships significantly predicted higher levels of prolonged grief risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 51 publications
1
19
0
6
Order By: Relevance
“…One of the 13 included studies did not report a correlational coefficient for the association but a written description of the association; however, once again, the authors kindly sent the output from the statistical analysis . Furthermore, the present study was able to update one previously reported study concerning the correlational coefficient of the relationship between avoidant attachment and anxious attachment and psychosocial variables, when the authors sent unpublished information on the correlational coefficient. Two studies investigating the association between caregiving styles and attachment were excluded from the quantitative analysis, because they used different caregiving style measures .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…One of the 13 included studies did not report a correlational coefficient for the association but a written description of the association; however, once again, the authors kindly sent the output from the statistical analysis . Furthermore, the present study was able to update one previously reported study concerning the correlational coefficient of the relationship between avoidant attachment and anxious attachment and psychosocial variables, when the authors sent unpublished information on the correlational coefficient. Two studies investigating the association between caregiving styles and attachment were excluded from the quantitative analysis, because they used different caregiving style measures .…”
Section: Resultsmentioning
confidence: 87%
“…The included studies were conducted in the USA (four), Canada (four), Italy (two), Australia (one), France (one), and Turkey (one) ( Table 1). Seven of the included studies involved terminally ill patients with cancer [7,26,47,48,[50][51][52], whereas two studies [53,54] reported on a sample of terminally ill patients with the majority suffering from cancer and the remaining from Alzheimer's disease and strokes. The last four studies involved a combination of patients with cancer with a good prognosis (no metastasis) and patients suffering from advanced disease [15,[55][56][57].…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…PCBD has been inserted in a special section of DSM-5 dedicated to conditions for further study (APA, 2013) . Horowitz has underlined the continuity between normal and pathological mourning on the basis of the intensity and duration of the experienced symptoms (Horowitz et al, 1993). Prigerson has focused attention on the persistence of a specific set of symptoms related to pain about the loss and to significant impairment of physical and mental health for at least six months (Lai et al, 2014a;Prigerson et al, 1995). There is a discrete overlap in the description of the two nomenclature, such as difficulty of adaptation, inability to move forward with lives, difficulty to fulfil responsibilities, somatic symptoms and disinterest in establishing new relationships (Horowitz et al, 1993(Horowitz et al, , 1997Lai et al, 2014a,b;Lombardo et al, 2012Lombardo et al, , 2014.…”
Section: Introductionmentioning
confidence: 98%
“…Few studies have tried to focus on the effects of concrete relationship relevant events such as relationship breakup (Kirkpatrick & Hazan, 1994) and interpersonal loss (Davila & Sargent, 2003;Trentini et al, 2015). In a recent study, it has been hypothesised that the emotional impact due to the grief could contribute to modify the stable aspects of personality as emotional and social abilities or attachment style (Hooper et al, 2012;Lai et al, 2007Lai et al, , 2014a.…”
Section: Introductionmentioning
confidence: 98%
“…Hamilton Depression Scale (HAMD) was used to assess the efficacy (Lai et al, 2015). HAMD contains 24 items, most of the items scores from 0 to 4 point in 5 levels as follows: absent (0 point), mild (1 point), moderate (2 point), severe (3 points), and very severe (4 point).…”
Section: Methodsmentioning
confidence: 99%